Making hstory happen - Morrison, Derrilyn E. (Cambridge Scholars Publishing, 2015)
Making History Happen: Caribbean Poetry in America examines Lorna Goodison's Turn Thanks (1999), McCallum's The Water Between Us (1999), and Claudia Rankine's Plot (2001) and Don't Let Me Be Lonely (2004). Engaging familiar themes and issues of time, language, and identity, the readings focus on
Includes bibliographical references and index
Keywords: Goodison; Lorna; McCallum; Shara; Rankine; Claudia; Turn thanks; Water between us; Plot; Don't let me be lonely; Caribbean poetry (English); Literary theory; Literary studies: poetry & poets; Literary studies: post-colonial literature; LITERARY CRITICISM; Poetry; Criticism; interpretation; etc